My meteorite, or, without the random there can be no new thing - Dodge, Harry (Penguin Books, 2020)
"As artist Harry Dodge initiates a research project about machine intelligence, he abruptly finds himself contending with the decline and death of his father from dementia, the renovation of a bewildering but powerful connection to his birth-mother, and the vicissitudes of artistic practice--its strange solitude and sociality. Under these pressures, the quotidian begins to tear, which allows a portal--perhaps activated by an iron meteorite Dodge orders on eBay--to open, and he rushes into it. The artist sets up an experiment: he vows to leave his studio and risk contact with unfamiliar people in order to put himself in touch with the magic that derives when humans connect. Grief and unease become catalysts for a reckoning with the vital forces of matter and--related--the bafflement of belonging. My Meteorite is a lyrical and provocative investigation into how we are shaped by ineffable forces we cannot know. Structured around a series of formative, formidable coincidences in Dodge's life, My Meteorite journeys from Barthes to "Blade Runner," from punk to Pale Fire. It is a wild, incandescent book that creates a literary universe of its own. At its heart lies the question of what it takes to love something, to deem its existence valuable (be it a robot, a stranger introduced as family, or a person with dementia). Blending the personal and the philosophical, the raw and the surreal, Harry Dodge re-enchants our world, illuminating the ways large and small coincidences make daily life shimmer into magic"--